EFEKTIVITAS SAVORING INTERVENTION TERHADAP WELL-BEING: STUDI META ANALISIS - Cita Tri Kusuma; Ananta Yudiarso (JIP (Jurnal Intervensi Psikologi), 2022)
High well-being is a protective factor against mental illness and psychopathology. To improve welfare, positive psychological interventions can be carried out, one of which is by enjoying the intervention. Purpose of this review is to evaluate the savoring intervention experiments and determine the effectiveness of the savoring interventions which can be used as evidence based in the practice of increasing well-being. This research was conducted by identifying appropriate and relevant literature. Identified randomized controlled trial from inception starts from May 2022 through proquest, google scholar, semantic scholar, and scopus. This meta-analysis research shows the results of effectiveness of savoring intervention on well-being which are in the medium category. The savoring intervention must also be strengthened with other additional interventions so that the result of effectiveness in influencing a person's well-being becomes greater and more significant. Differences in participant characteristics and the amount of literature included in this study are the weaknesses of this study.